Enhancing anthropometric skills and nutrition counseling through mentoring for adolescent Posbindu cadres - Sri Noor Mintarsih; Ria Ambarwati; Zuhria Ismawanti; Sunarto Sunarto; Mardiana Mardiana; Anggi Ariana Wijayanti (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2025)
Noncommunicable diseases (NCDs) pose a significant health threat to adolescents, including those in Semarang. The prevalence of NCD risk factors among high school students in Semarang highlights the urgent need for effective intervention. Empowering peer counselors as cadres through the Posbindu program can facilitate early detection of NCD risk factors. However, cadres’ capacities for anthropometry and nutritional counseling remain inadequate. This study aimed to evaluate the impact of a structured mentoring program on enhancing knowledge and skills of adolescent Posbindu cadres in anthropometric measurements and nutrition counseling. This quasi-experimental study used a pretest-posttest control group design. A total of 36 students from grades 11 and 12 in two high schools in Semarang were recruited as cadres. The intervention consisted of lectures, demonstrations, and booklets. Data were collected through questionnaires measuring knowledge, anthropometric skills, and counseling abilities. A multivariate independent t-test was used for the statistical analysis. The mentoring program significantly improved knowledge, anthropometric skills, and counseling performance (p<0,001). Mentoring contributed to a 42% improvement in knowledge, 62% in anthropometric skills, and 64% in counseling abilities. Mentoring is an effective strategy for strengthening the competencies of Posbindu cadres in performing anthropometric assessments and providing nutrition counseling to support the early detection of NCD risk factors among adolescents.